Dual impact of information technology and dining environment: the potential mechanisms of takeout services on college student health - Yang, Qi (Frontiers in Public Health, 2025)
With the development of information technology and the popularization of the O2O business model, food delivery services have become a primary dietary choice for university students. This study, based on the social-ecological model, environmental psychology, and behavioral decision theory, aims to explore the mechanisms by which food delivery culture and campus dining environments influence obesity risk among university students, providing a basis for campus dietary management and public health policies. The study involved eight universities in Changsha, collecting 518 questionnaires on dietary behaviors, self-reported BMI, and weight change data. It also integrated data from Gaode Maps and food delivery platforms to assess the characteristics of dining environments. Multiple regression and logistic regression models were used to analyze the relationships between dining environments, food delivery frequency, and health outcomes. The results showed that food delivery frequency was significantly associated with economic status (regression coefficient = 0.418, p < 0.001), with students with higher living expenses being more likely to opt for food delivery. There was a significant negative correlation between healthy food delivery option scores and BMI (standardized coefficient = −0.110, p < 0.05), indicating that students who chose healthier food delivery options had lower BMI. Longer food delivery times (regression coefficient = −0.257, p = 0.052) and poorer cafeteria accessibility (regression coefficient = 0.433, p < 0.001) significantly increased food delivery frequency. Additionally, students in suburban universities had higher BMI (23.45 kg/m2) than those in urban universities (22.23 kg/m2), primarily due to lower availability of healthy dining options in suburban areas. The study indicates that food delivery culture, through its convenience and diversity, reinforces a tendency to consume high-calorie foods, increasing the risk of obesity. It is recommended to optimize on-campus healthy dining facilities and introduce health-focused recommendation systems on food delivery platforms to promote healthier behaviors among university students.